Analisis Perbandingan Fonem Bahasa Sunda Dan Bahasa Indonesia - Ayu Lestari; Aprillya Nurizki; Hana Ghina Hanifah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2023)
This research focuses on a comprehensive comparison of phonemes between Sundanese and Indonesian languages. The analysis employs content analysis to delineate the intricate differences between the two languages. Sundanese, as revealed in the study, comprises seven vowel phonemes, whereas Indonesian has five primary vowels. Vowel classification in both languages involves lip position, tongue's front-back movement, and tongue height during pronunciation. Sundanese has 18 consonant phonemes, while Indonesian possesses 21 consonant phonemes. Interestingly, despite Sundanese having 29 vowels, some are unable to occur consecutively with other vowels. Conversely, in Indonesian, words with diphthongs, i.e., a sequence of two vowels in one syllable, are considered separate cases. Another significant difference is the presence of an additional phoneme in Sundanese, namely /é/, which is absent in Indonesian. The existence of this phoneme adds complexity to Sundanese phonological patterns. Additionally, noticeable differences in consonant phonemes exist, with Sundanese having only 18, while Indonesian has 21, creating intriguing phonetic diversity between the two languages.